2021
DOI: 10.1002/jbt.22776
|View full text |Cite
|
Sign up to set email alerts
|

Syringic acid regulates suppression of the STAT3/JNK/AKT pathway via inhibition of human ovarian teratoma cancer cell (PA‐1) growth—in vitro study

Abstract: Among the various gynaecological cancers, ovarian cancer (OC) is the third most severe cancer worldwide affecting women. Syringic acid (SRA) exhibits several hypoglycaemia, antioxidant, and anti-inflammatory properties. The study aimed to examine the proapoptotic activities of SRA on OC in PA-1 cells. SRA has been shown to decrease cell viability, increase the rate of cell apoptosis, and cause mitochondrial membrane potential to dissipate and induce over-accumulation of intracellular reactive oxygen species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It has been reported in the literature that these five ingredients possess anti-cancer properties. Specifically, syringic acid targets glioblastoma, gastric cancer, and ovarian teratoma cancer [35][36][37]; kirenol exhibits efficacy against thyroid cancer, cancer, and myeloid leukemia [38][39][40]; chlorogenic acid shows potential against pancreatic cancer, colorectal cancer, ovarian cancer, and oral squamous carcinoma [41][42][43][44]; p-coumaric acid demonstrates activity on epidermoid carcinoma, colorectal cancer, osteosarcoma, and glioblastoma [45][46][47][48]; syringaldehyde is effective against breast cancer [49]. However, the impact of these ingredients on liver cancer needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the literature that these five ingredients possess anti-cancer properties. Specifically, syringic acid targets glioblastoma, gastric cancer, and ovarian teratoma cancer [35][36][37]; kirenol exhibits efficacy against thyroid cancer, cancer, and myeloid leukemia [38][39][40]; chlorogenic acid shows potential against pancreatic cancer, colorectal cancer, ovarian cancer, and oral squamous carcinoma [41][42][43][44]; p-coumaric acid demonstrates activity on epidermoid carcinoma, colorectal cancer, osteosarcoma, and glioblastoma [45][46][47][48]; syringaldehyde is effective against breast cancer [49]. However, the impact of these ingredients on liver cancer needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…SyA was evocative to be used as a prospective therapeutic drug with potential application for the treatment of OC due to the encouraging anticancer effect. Yang et al [ 103 ] reported SyA-mediated suppression of STAT3/JNK/AKT pathway along with significant growth inhibition in human ovarian teratoma cancer cells (PA-1). SyA significantly modified the apoptosis-related protein expression level, viz., caspase-3, 8, 9, Bax, and Bcl-2 in PA-1 cells.…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%
“…SyA significantly modified the apoptosis-related protein expression level, viz., caspase-3, 8, 9, Bax, and Bcl-2 in PA-1 cells. Furthermore, SyA treatment significantly reduced the levels of cancer promoting proinflammatory cytokines TNF, IL-2, IL-6, and IL-10 in ovarian cancer cells [ 103 ]. The chemoprotective action of SyA on cyclophosphamide-induced ovarian damage via an inflammatory pathway was also reported by Liu et al [ 104 ].…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%
See 2 more Smart Citations